Answer:
x= 20
Step-by-step explanation:
Answer: False
Explanation: 4(-4) + (-9)=-36, 4•-4= -16 - 9= -25 not -36
Answer:
The solution for the given expression x ix 6.
Step-by-step explanation:
![4x + 1 = 5x + (-5)](https://tex.z-dn.net/?f=4x%20%2B%201%20%3D%205x%20%2B%20%28-5%29%20)
Solution:
Step 1: Adding (-4x) on both sides
![4x + 1 +(-4)= 5x + (-5)+(-4x)](https://tex.z-dn.net/?f=4x%20%2B%201%20%2B%28-4%29%3D%205x%20%2B%20%28-5%29%2B%28-4x%29%20)
![1=-5+1x](https://tex.z-dn.net/?f=1%3D-5%2B1x)
Step 2: Adding (5) on both sides:
![1+5=-5+1x+5](https://tex.z-dn.net/?f=1%2B5%3D-5%2B1x%2B5)
![6=x](https://tex.z-dn.net/?f=6%3Dx)
The solution for the given expression x ix 6.